2009
DOI: 10.1103/physrevb.80.104501
|View full text |Cite
|
Sign up to set email alerts
|

Superconducting properties of the oxygen-deficient iron oxyarsenideTbFeAsO1δfrom underdoped to overdoped compositions

Abstract: A wide-range doping was achieved by a high-pressure method for TbFeAsO 1−␦ from "underdoped" to "overdoped" superconducting compositions throughout the optimized superconductivity ͑T c of 44 K͒. T c vs ␦ shows a dome-shaped feature, while T c vs the lattice constant likely follows a unique empirical curve over the doping range. The relatively large amount of oxygen vacancies up to ϳ0.3 per the formula unit was introduced possibly because of the smaller replacement Tb than the other Ln ͑rare-earth element͒ in t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(23 citation statements)
references
References 33 publications
2
20
1
Order By: Relevance
“…In The anisotropic lattice feature is remarkably contrast with what was found for LaFeAsO 1-δ [26] and TbFeAsO 1-δ [27], in which the unit cell is isotropically contracted with increasing amount of the oxygen vacancies. Nevertheless, the systematic lattice change is indicative of successful doping of the oxygen vacancies into the structure, although we were unable to measure the net oxygen concentration by a chemical method because of the toxic effects.…”
Section: Results and Discusioncontrasting
confidence: 46%
See 2 more Smart Citations
“…In The anisotropic lattice feature is remarkably contrast with what was found for LaFeAsO 1-δ [26] and TbFeAsO 1-δ [27], in which the unit cell is isotropically contracted with increasing amount of the oxygen vacancies. Nevertheless, the systematic lattice change is indicative of successful doping of the oxygen vacancies into the structure, although we were unable to measure the net oxygen concentration by a chemical method because of the toxic effects.…”
Section: Results and Discusioncontrasting
confidence: 46%
“…About 20 mg of the samples were full oxidized at 1500 ºC for 24h in air then were slowly cooled to room temperature. [27], it is suggested that the anomaly is due to formation of the spin density wave (SDW). It is interesting that a comparable anomalous feature of the electrical resistivity, even it is fairly weak, can be seen in the data reported independently by others [24].…”
Section: Results and Discusionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding LaFeAsO 1−␦ , the tetragonal lattice parameters a and c decrease with increasing ␦ as well as what was found for the compounds TbFeAsO 1−␦ . 36 This probably reflects combination of Coulomb attractive forces between the charged ͓LaO 1−␦ ͔ 1+2␦ and ͓FeAs͔ 1−2␦ layers and amount of vacate sites for oxygen atoms. In sharp contrast to the observation, the Zn substitution resulted in an anisotropic change in the lattice parameters: c of LaFe 1−x Zn x AsO 0.85 increases ͑+0.02% at Zn 0.01 ͒ while a decreases much efficiently ͑−0.08%͒ over the substitution.…”
Section: Resultsmentioning
confidence: 99%
“…The poor quality persisted exceptionally at ␦ =0 ͑not due to a run-to-run error͒ as observed in the high-pressure synthesis of TbFeAsO 1−␦ . 36 It should be emphasized that the optimally carrier-doped samples ͑␦ = 0.15͒ with and without Zn were all prepared under the same high-pressure condition.…”
Section: Methodsmentioning
confidence: 99%